MBRS-59. MiR-1253, A CANDIDATE TUMOR SUPPRESSOR microRNA IN NON-SHH/WNT MEDULLOBLASTOMA. Issue 2 (22nd June 2018) - Kanchan, Ranjana; Perumal, Naveen Kumar; Naseer, Wasim; Perry, Deborah; Batra, Surinder; Mahapatra, Sidharth
Abstract: Medulloblastoma (MB) is the most common malignant pediatric tumor of the central nervous system (CNS) and a leading cause of childhood morbidity and mortality. Haploinsufficiency of 17p13.3 is reported in up to 50% of human MB cases. Included within this locus is miR-1253, which is exclusively expressed in the brain and an important regulator of bone morphogenic proteins that play a critical role in cerebellar development. Recently, two oncogenic targets of miR-1253, i.e. TGIF2 and ALX4, were identified in SHH medulloblastoma. Based upon these observations, we hypothesized that miR-1253 may be a putative tumor suppressor gene that undergoes epigenetic silencing in pediatric medulloblastoma. We first discovered reduced expression of miR-1253 in 24 clinical specimens and in 7 medulloblastoma cell lines. We then learned that miR-1253 silencing is accomplished via hypermethylation; expectedly, de-methylation of miR-1253 using 5-AzaC, resulted in recovery of expression with a subsequent decline in MB cell proliferation. MiR-1253 restoration was further concomitant with activation of apoptotic pathways and cell cycle arrest at G0 /G1 phase. Moreover, miR-1253 overexpression led to a reduction in cell proliferation, colony formation, migration and invasive potential of MB tumor cell lines. Taken together, these data suggest that miR-1253 may possess tumor suppressor qualities, i.e. 1) loss of expression via epigenetic silencing and 2) negative trophic effects on tumor cell growth and migration. This would be the first time such an effect has been attributed to miR-1253 in the context of medulloblastoma.